Match games: exploring the match between novice teachers and induction coaches. Issue 1 (19th May 2021) - Kwok, Andrew; Rios, Ambyr Ruth; Keese, Jeffrey; Suárez, Mario; Worley, Cristina; Patterson, Megan; Mitchell, Douglas; Huston, Debbee
ABSTRACT: This mixed methods study investigates novice teacher and coach survey responses from a two-year induction programme to learn more about what makes a good match. We qualitatively analyse comments from all novice teachers and coaches who were paired across years and find shared themes of structural, professional, and personality similarities as well as the importance of coaching support prominent throughout novice teacher responses. We also use logistic regression to indicate that novice teachers' ratings of coaching skills and coaches' beliefs about the induction programme fitting within vertical professional development were positive and significant predictors of perceptions of being well matched. Findings have implications for induction programmes on how to match their coaches with novice teachers to enhance teacher development.